Striatal fibrinogen extravasation and vascular degeneration correlate with motor dysfunction in an aging mouse model of Alzheimer’s disease - Berk-Rauch, Hanna E.; Choudhury, Arnab; Richards, Allison T.; Singh, Pradeep K.; Chen, Zu-Lin; Norris, Erin H.; Strickland, Sidney; Ahn, Hyung Jin (Frontiers in Aging Neuroscience, 2023)
Alzheimer’s Disease (AD) patients exhibit signs of motor dysfunction, including gait, locomotion, and balance deficits. Changes in motor function often precede other symptoms of AD as well as correlate with increased severity and mortality. In the present study, we investigated the relationship between cerebrovascular impairment and motor dysfunction in a mouse model of AD (Tg6799). We found an age-dependent increase of extravasated fibrin(ogen) deposits in the cortex and striatum of AD mice. Interestingly, there was significantly decreased cerebrovascular density in the striatum of the 15-month-old as compared to 7-month-old AD mice. We also found significant demyelination and axonal damage in the striatum of aged AD mice. We analyzed striatum related motor function and anxiety levels of AD mice at both ages and found that aged AD mice exhibited a significant impairment of motor function but not in the younger AD mice. Thus, our finding suggests an enticing correlation between extravasated fibrinogen, cerebrovascular damage of the striatum and motor dysfunction in an AD mouse model, suggesting a possible mechanism underlying motor dysfunction in AD.